ANALISIS KONVERGENSI EKONOMI PADA LEVEL KAWASAN DAN NASIONAL SERTA FAKTOR-FAKTOR YANG MEMENGARUHINYA - Roseta Afrina Arsyanti; Tri Nugrahadi (Seminar Nasional Official Statistics, 2020)
Inequality economic development causes an economic imbalance between region in Western Indonesia Region (KBI), Eastern Indonesia Region (KTI) and National (Indonesia). The index williamson of KBI, KTI, and National for 2011-2018 show that inequality is still high. An analysis to show whether the economy will converge or diverge should be done. This study aims to provide an overview of the economy and analyze the occurrence of economic convergence at KBI, KTI, and National. This study use panel data analysis approach at KBI (17 provinces), KTI (16 provinces), and National (33 provinces) from 2011 to 2018. The results indicate that the economy at KBI and KTI are still lame. The dispersion of per capita income is decreased or sigma convergence is occurred at KTI and National, while at KBI is not occurred. This study emphasis confirm that absolute and conditional beta convergence is occurred at KBI, KTI, and National. The conditional beta convergence rate shows that regional characteristics are able to accelerate the convergence rate. Variables that positively significant affect economic growth and the convergence process at National level are the length of road, PMTDB, proportion of the workforce employed, and average length of schooling; at the KBI level are the length of road, PMTDB, and the proportion of the workforce employed; whereas at the KTI level are the length of road and the average length of schooling.